Implementation of the Assurance, Relevance, Interest, Assessment, Satisfaction (ARIAS) Learning Model in Improving Student Learning Outcomes in PAI Subjects - Fajariyatul Amelia; Khoirun Nisa; Rizqiyah; Rodiyah; Maris Din Nafis (Global Action and Education for Society, 2025)
There are two main issues being studied in this research, the first being the low academic performance of students, and the second being the lack of interest in learning and understanding among ninth-grade students at SMP Negeri 2 Palengaan. The problem formulation in this research is: 1.) How is the implementation of the Arias model in improving student learning outcomes in Islamic Religious Education at SMP Negeri 2 Palengaan? 2.) What are the inhibiting and supporting factors in the implementation of the ARIAS learning model in improving student learning outcomes in Islamic Religious Education at State Junior High School 2 Palengaan? The type of research in this study uses a qualitative approach based on the research results obtained in the form of descriptive data. The data collection procedures used are observation, interviews, and documentation, with the data sources for this research being the school principal, PAI subject teachers, and students. Meanwhile, the data analysis in this study uses data reduction, data presentation, and data verification. From the research results obtained, it shows that the ARIAS learning model is quite effective in improving student learning outcomes in Islamic Religious Education subjects in the 9th grade at SMP Negeri 2 Palengaan. Proven by supporting factors, namely students feel enthusiastic, comfortable, happy, not easily bored, and there is an improvement in learning outcomes, which is also supported by the availability of adequate facilities and learning media at SMP Negeri 2 Palengaan. Meanwhile, the inhibiting factor is the lack of time allocation for the subject of Islamic Religious Education provided by the curriculum. The researcher hopes that the ARIAS learning model can be considered as one of the models in the teaching and learning process at SMP Negeri 2 Palengaan, and can enhance students' active involvement in the learning process.